Architectuur en verbeelding = architecture and imagination. - Brand, J.; Janselijn, H. (Zwolle : Waanders, 1989)
Armajani, Siah ; Avvakumov, Yuri ; Baldessari, Luciano ; Van Berkel, Ben ; Brancusi, Constantin ; Branzi, Andrea ; Brodsky, Alexander ; Brown, Tony ; Bunschoten, Raoul ; Cantafora, Arduino ; De Chirico, Giorgio ; Coenen, Jo ; Depero, Fortunato ; Descombes, Georges ; van Doesburg, Theo ; Eikelenboom, Alfred ; Eisenman, Peter ; Fontana, Lucio ; Gehry, Frank ; Gerdes, Ludger ; Graham, Dan ; Grassi, Giorgio ; Haus-Rucker-Co ; Hejduk, John ; Hollein, Hans ; Janselijn, Han ; Kirkeby, Per ; Koolhaas, Rem ; Körmeling, John ; Krier, Leon ; Laan, Dom H. Van Der ; Le Corbusier ; Leonidov, Ivan ; Libera, Adalberto ; Libeskind, Daniel ; Lissitzky, El ; Loos, Adolf ; Malevich, Kasimir ; Matta-Clark, Gordon ; Melnikov, Konstantin ; Mendini, Alessandro ; Mies van der Rohe, Ludwig ; Mollino, Carlo ; Navarro Baldeweg, Juan ; de Pavert, Jan van ; van Ravesteyn, Sybold ; Rietveld, Gerrit ; Rossi, Aldo ; Scarpa, Carlo ; Schütte, Thomas ; Scolari, Massimo ; Sironi, Mario ; Sottsass, Ettore ; Tatlin, Vladimir ; Taut, Bruno ; Tschumi, Bernard ; Utkin, Ilya ; Venturi, Robert ; Wewerka, Stefan ; Wilson, Peter
boek